Development of a novel walkability index for London, United Kingdom: cross-sectional application to the Whitehall II Study. (December 2016) - Stockton, Jemima; Duke-Williams, Oliver; Stamatakis, Emmanuel; Mindell, Jennifer; Brunner, Eric; Shelton, Nicola
Abstract Background Physical activity is essential for health; walking is the easiest way to incorporate activity into everyday life. Previous studies report positive associations between neighbourhood walkability and walking but most focused on cities in North America and Australasia. Urban form with respect to street connectivity, residential density and land use mix—common components of walkability indices—differs in European cities. The objective of this study was to develop a walkability index for London and test the index using walking data from the Whitehall II Study.  Methods A neighbourhood walkability index for London was constructed, comprising factors associated with walking behaviours: residential dwelling density, street connectivity and land use mix. Three models were produced that differed in the land uses included. Neighbourhoods were operationalised at three levels of administrative geography: (i) 21, 140 output areas, (ii) 633 wards and (iii) 33 local authorities. A neighbourhood walkability score was assigned to each London-dwelling Whitehall II Study participant (2003–04, N  = 3020, mean ± SD age = 61.0 years ± 6.0) based on residential postcode. The effect of changing the model specification and the units of enumeration on spatial variation in walkability was examined. Results There was a radial decay in walkability from the centre to the periphery of London. There was high inter-model correlation in walkability scores for any given neighbourhood operationalisation (0.92–0.98), and moderate-high correlation between neighbourhood operationalisations for any given model (0.39–0.70). After adjustment for individual level factors and area deprivation, individuals in the most walkable neighbourhoods operationalised as wards were more likely to walk >6 h/week (OR = 1.4; 95 % CI: 1.1–1.9) than those in the least walkable. Conclusions Walkability was associated with walking time in adults. This walkability index could help urban planners identify and design neighbourhoods in London with characteristics more supportive of walking, thereby promoting public health.